Incidence and pattern of adverse drug reactions among pediatric inpatients: A prospective observational study. - Sekhar, Duggi Chandra; Reddy, SOVS Satish; Reddy T, Rajasekhar (Student's Journal of Health Research Africa, 2025)
Background: Adverse drug reactions (ADRs) are a significant cause of morbidity in the pediatric population due to age-specific pharmacodynamic and pharmacokinetic variations. Active surveillance is crucial to understanding the pattern and burden of ADRs in this vulnerable group. Objectives: To determine the incidence, spectrum, causality, and severity of adverse drug reactions in pediatric patients at a tertiary care hospital. Methods: A prospective observational study was conducted over 12 months (March 2024–February 2025) in the Department of Pediatrics, Santhiram Medical College, Nandyal, Andhra Pradesh. A total of 100 inpatients aged <12 years were enrolled and monitored daily for suspected ADRs, which were documented and analyzed. Severity was graded using the Modified Hartwig and Siegel Scale, and causality was assessed by WHO-UMC criteria. Results: Out of 100 children, 26 (26%) experienced at least one ADR, accounting for 35 reactions. Infants aged <1 year showed the highest incidence (30%), with a slight male predominance. Antibiotics (48.6%) were the most frequently implicated drug class, followed by antiepileptics (20%) and NSAIDs (14.3%). Gastrointestinal (31.4%) and dermatological (25.7%) systems were most affected. Most ADRs were mild (65.7%), while 28.6% were moderate and 5.7% severe. According to WHO-UMC criteria, 40% were classified as possible, 37.1% as probable, and 22.9% as certain. Conclusion: A significant proportion of pediatric inpatients experienced ADRs, predominantly associated with antibiotics and antiepileptics. Most were mild to moderate and resolved without sequelae. The study underscores the importance of proactive monitoring and reporting systems to improve pediatric medication safety. Recommendations: Routine pharmacovigilance training and electronic monitoring should be integrated into pediatric care to reduce preventable adverse drug events.